The USAID-Priority Partnership Program in Education: An Emerging Case Study in Batu City, Indonesia's East Java Province - Dwiastuti, Esty; Zauhar, Soesilo; Mindarti, Lely Indah; ., Suryadi (Journal of Ecohumanism, 2024)
The USAID-Priority Partnership program's implementation in the education sector is impacted by the cooperation of multiple actors and refers to interrelated principles at every stage of implementation, such as the principles of equality, openness, and mutual benefit. Dynamically and mutually supportive of all principles related to each other, schools can improve the performance of the quantity and quality of education services in a sustainable manner. Participants in the USAID-Priority Partnership program are organized, strategic intervention ideas are developed, coalitions are formed, strategies are reviewed and adopted, implemented, monitored, and evaluated, and their implementation is impacted by both enabling and impeding factors. In the implementation of the USAID-Priority Partnership program, the authors found a positive impact on the reform of the education system. Schools can implement the USAID-Priority Partnership program to improve education services if all stakeholders in the education sector can implement curriculum-based learning methods, which is a central policy and can have a positive impact on the educational system. This research uses a qualitative research type. This study's research focusses on the following topics: (1) how the USAID-Priority Partnership Program is implemented in terms of enhancing learning quality, governance, and coordination amongst institutions; (2) the role of each actor; (3) factors that facilitate or hinder the implementation of the USAID-Priority Partnership Program; and (4) the USAID-Priority Partnership Model in the field of education from the standpoint of public service. Interview-derived data and information. This study uses qualitative thinking that is empirically inductive. Data analysis uses the grand theory of public service with a public-private partnership (PPP) theoretical approach.